Life cycle resilience assessment of RC frame structures considering multiple-hazard. (October 2022) - Li, Yiming; Fu, Zhijun; Tan, Ping; Shang, Jiying; Mi, Peng
Abstract: Corrosion can lead to the seismic performance deterioration of RC structures, however, the corrosion effects on the seismic risks and resilience are poorly understood. This paper proposes a framework for assessing the life cycle resilience of RC structures under multi-hazards. The framework integrates the probabilistic corrosion model, seismic hazard model, fragility, seismic risk assessment, resilience assessment, and resilience rating model. The time-variant economic losses that consist of the repair cost and downtime loss are assumed as the functionality indicators. The repair time and idle time associated with impeding factors are considered in the recovery time. To accurately assess the seismic resilience of uncorroded and corroded structures, an innovative recovery model that is validated with recovery data in the previous work is proposed. The resilience rating method that considers economic loss, recovery time, and seismic resilience is suggested to assess the final resilience level. The proposed framework is applied to a four-story reinforced concrete frame office building located in the coastal area where chloride attacks are extreme. The results show that the corrosion increases the seismic risk and decreases the resilience of buildings, which reveals the importance of the life cycle resilience assessment of buildings under multi-hazards. The proposed framework can be modified to incorporate other hazards such as floods and typhoons to assess life cycle disaster resilience.